New genetic variants of LATS1 detected in urinary bladder and colon cancer - Saadeldin, Mona K.; Shawer, Heba; Mostafa, Ahmed; Kassem, Neemat M.; Amleh, Asma; Siam, Rania (Frontiers in Genetics, 2015)
LATS1, the large tumor suppressor 1 gene, encodes for a serine/threonine kinase protein and is implicated in cell cycle progression. LATS1 is down-regulated in various human cancers, such as breast cancer, and astrocytoma. Point mutations in LATS1 were reported in human sarcomas. Additionally, loss of heterozygosity of LATS1 chromosomal region predisposes to breast, ovarian and cervical tumors. In the current study, we investigated LATS1 genetic variations including single nucleotide polymorphisms (SNPs), in 28 Egyptian patients with either urinary bladder or colon cancers. The LATS1 gene was amplified and sequenced and the expression of LATS1 at the RNA level was assessed in 12 urinary bladder cancer samples. We report, the identification of a total of 29 variants including previously identified SNPs within LATS1 coding and non-coding sequences. A total of 18 variants were novel. Majority of the novel variants, 13, were mapped to intronic sequences and un-translated regions of the gene. Four of the five novel variants located in the coding region of the gene, represented missense mutations within the serine/threonine kinase catalytic domain. Interestingly, LATS1 RNA steady state levels was lost in urinary bladder cancerous tissue harboring four specific SNPs (16045+41736 + 34614 + 56177) positioned in the 5’UTR, intron 6, and two silent mutations within exon 4 and exon 8 respectively. This study identifies novel single-base-sequence alterations in the LATS1 gene. These newly identified variants could potentially be used as novel diagnostic or prognostic tools in cancer.